LAMA PEREDAMAN PERANGKAP LIPAT YANG EFEKTIF UNTUK PENANGKAPAN KEPITING BAKAU (Scylla sp.) - Hafinuddin Hafinuddin; Ikhsan Saputra; Mahendra Mahendra (JURNAL PERIKANAN TROPIS, 2016)
Fishing of mud crab (Scylla sp.) is using many fishing gear type, one of that i.e traps. Immersion periods is one of aspect to consideration to catching mud crab. Therefore, purpose of this study is to know immersion periods to catching mud crab efectively. This study was conducted on September 2016 in estuaries waters, Kuala Bubon Village, Samatiga  Sub District, Aceh Barat District. Methods of this  study is experimental fishing method and fully randomized design have used for this study. Immersion periods is treatments, i.e 4 hours, 8 hours and 12 hours with  3 replicates. An analysis of variance (ANOVA) at significant level 95% (p < 0.05) was selected to assess the statistical significance of the treatment differences. All data was performed with SPSS 18.0.0 software. Results of this study show that fish catching of mud crabs not siggnificant difference for every treatments (p>0.05). However, descriptive analysis show that immersing with 12 hours more efective than of 4 hours and 8 hours. This study is important for traps’s fishermen to catching mud crabs, where hauling of traps can be applied in the morning (immersing with 12 hours).